2021
DOI: 10.1016/j.ajem.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID-19 pandemic on emergency department visits for serious cardiovascular conditions

Abstract: Objective We examine how emergency department (ED) visits for serious cardiovascular conditions evolved in the coronavirus (COVID-19) pandemic over January–October 2020, compared to 2019, in a large sample of U.S. EDs. Methods We compared 2020 ED visits before and during the COVID-19 pandemic, relative to 2019 visits in 108 EDs in 18 states in 115,716 adult ED visits with diagnoses for five serious cardiovascular conditions: ST-segment elevation myocardial infarction (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 23 publications
(25 reference statements)
4
52
0
1
Order By: Relevance
“…The present study did not find any difference in the total number of stroke admissions between the two study periods although a decline in the April 2020 correlated with the increasing surge of COVID-19 cases and the acute lockdown period starting from late March 2020. Earlier reports have suggested a significant decline in stroke and coronary artery admissions, possibly related to the reduced number of patients reporting to the hospitals due to fear of COVID-19 or overwhelmed health systems not prioritizing such admissions [ [11] , [12] , [13] , [14] , [15] ]. It is possible that since most of the centres were not admitting COVID positive patients, the usual number of stroke admissions remained constant.…”
Section: Discussionmentioning
confidence: 99%
“…The present study did not find any difference in the total number of stroke admissions between the two study periods although a decline in the April 2020 correlated with the increasing surge of COVID-19 cases and the acute lockdown period starting from late March 2020. Earlier reports have suggested a significant decline in stroke and coronary artery admissions, possibly related to the reduced number of patients reporting to the hospitals due to fear of COVID-19 or overwhelmed health systems not prioritizing such admissions [ [11] , [12] , [13] , [14] , [15] ]. It is possible that since most of the centres were not admitting COVID positive patients, the usual number of stroke admissions remained constant.…”
Section: Discussionmentioning
confidence: 99%
“…Our study team has published several studies using this database (<1%). 5,6,10,12,13 Facilities included small-(<30,000 visits per year, n¼40), medium-(30,000 to 59,999 visits per year, n¼56) and large-hospital based EDs (!60,000 visits per year, n¼16) and freestanding EDs (n¼24). Freestanding ED volumes were comparable to those of small-hospital based EDs, but we examined freestanding EDs separately given their different organizational structure.…”
Section: Study Design and Settingsmentioning
confidence: 99%
“…3,4 ED visits declined for both low-acuity and high-acuity conditions, including acute myocardial infarction, stroke, heart failure, and substance use disorders. 5,6 Since that time, ED visit rates have partially recovered, but they remain substantially below 2019 levels. Potential contributors to fewer ED visits include less communicable disease and injury due to public health measures, including social distancing, mask wearing, and school/business closures.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Studies from the emergency medicine literature have reported significantly lower overall patient visits and admissions during the pandemic [ [20] , [21] , [22] , [23] , [24] , [25] , [26] ] as well as lower volumes of patients with cardiac emergencies. [ [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. But these studies have not examined delays in processes of care of STEMI patients within the ED.…”
Section: Introductionmentioning
confidence: 99%